2010
DOI: 10.1037/a0018939
|View full text |Cite
|
Sign up to set email alerts
|

Exploring urban students’ constructions about school, work, race, and ethnicity.

Abstract: This qualitative study is an exploration of 32 urban high school students' narratives about the connection between school, work, and societal expectations of their future success related to their racial and ethnic background. The sample varied along 2 contextual dimensions: participation in a psychoeducational intervention (Tools for Tomorrow) and developmental status (i.e., half the sample were 9th-grade students and the other half were 12th-grade students). Using consensual qualitative research, the narrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Most participants found the program to be helpful. In terms of revealing a future orientation and a basic connection between school and work, these results are consistent with Blustein et al’s (2010) findings in a qualitative study of 32 diverse urban youth.…”
Section: Discussionsupporting
confidence: 87%
“…Most participants found the program to be helpful. In terms of revealing a future orientation and a basic connection between school and work, these results are consistent with Blustein et al’s (2010) findings in a qualitative study of 32 diverse urban youth.…”
Section: Discussionsupporting
confidence: 87%
“…In their interview responses, the participants shared few examples of role models in investigative domains. From an social–cognitive career theory perspective (Lent et al, 1994, 2000), the investigative interests, self-efficacy beliefs, and outcome expectations of these youth may have been constrained or prematurely foreclosed by their perceptions of barriers, such as discrimination and low socioeconomic status (Blustein et al, 2010). These potential hypotheses might be explored with individuals to inform relevant vocational intervention strategies to promote resilient success-learning experiences in investigative domains.…”
Section: Discussion and Implications For Theory Research And Practicementioning
confidence: 99%
“…Research–service collaborations of counseling psychologists with schools have made significant contributions to inform evidence-based practice (Blustein et al, 2010; Perry, DeWine, Duffy, & Vance, 2007; Romano & Kachgal, 2004; Scheel, Madabhushi, & Backhaus, 2009). There are several challenges and benefits of research–service collaborations.…”
Section: Discussion and Implications For Theory Research And Practicementioning
confidence: 99%
“…Many authors have proposed that culturally and contextually relevant career development practices be used with traditionally marginalized populations (Guiffrida & Douthit, 2010;Hansen, 2003;Pope, 2003;Trainor, Lindstrom, Simon-Burroughs, Martin, & Sorrells, 2008;West-Olatunji et al, 2010). For example, Blustein et al (2010) suggested that "career development education programs include specific attention to issues pertaining to race, culture, and ethnicity" (p. 253). While such suggestions likely have merit and relevance within the current economic crisis, they have not specifically addressed the career-and workrelated challenges of traditionally marginalized populations in this economic climate.…”
Section: Career Development Interventions For Traditionally Marginalimentioning
confidence: 99%